2012
DOI: 10.1186/1471-2164-13-647
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals unique metabolic features in the Cryptosporidium parvum Oocysts associated with environmental survival and stresses

Abstract: BackgroundCryptosporidium parvum is a globally distributed zoonotic parasite and an important opportunistic pathogen in immunocompromised patients. Little is known on the metabolic dynamics of the parasite, and study is hampered by the lack of molecular and genetic tools. Here we report the development of the first Agilent microarray for C. parvum (CpArray15K) that covers all predicted ORFs in the parasite genome. Global transcriptome analysis using CpArray15K coupled with real-time qRT-PCR uncovered a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 40 publications
4
48
1
Order By: Relevance
“…It has been reported that human cells submitted to UV stress in general show low alternation in transcription levels (Rieger and Chu, 2004). This was also observed for E. histolytica (Weber et al, 2009) and C. parvum (Zhang et al, 2012) and now also in this study. The question is if this low alteration in transcription will be reflected on the protein synthesis in the cell.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It has been reported that human cells submitted to UV stress in general show low alternation in transcription levels (Rieger and Chu, 2004). This was also observed for E. histolytica (Weber et al, 2009) and C. parvum (Zhang et al, 2012) and now also in this study. The question is if this low alteration in transcription will be reflected on the protein synthesis in the cell.…”
Section: Discussionsupporting
confidence: 89%
“…The chosen recovery time was based on a similar study in E. histolytica where it was shown that the transcriptional response was most evident after 3 hours (Weber et al, 2009). In addition, our chosen recovery time falls in between those used in a study on UV-C treatment on Cryptosporidium oocyst in which significant transcriptional regulation at both 0.5 hours and 5 hours post-radiation (Zhang et al, 2012) was shown. Our transcriptional analysis showed that 108 genes in trophozoites and 202 genes in cysts changed their expression upon UV-C irradiation more than 1.5-fold and 85 genes showed more than 2-fold changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations